Impact of gender targeting in ICT hubs: Cluster randomized controlled trial in Malawi - Ragasa, Catherine (International Food Policy Research Institute, 2023)
Access to information and improved technologies is a major constraint for improving agricultural productivity and incomes in many agriculture-based economies, including Malawi. A combination of digital agricultural extension services and facilitation of group learning 50 BOOK OF ABSTRACTS through ICT hubs is being piloted in Malawi under the Scaling Up Radio and ICTs for Enhanced Extension Delivery (SRIEED) II project. Gender messaging and targeting are incorporated in this digital extension provision and group learning. Designed as a clusteredrandomized controlled trial, this study aims to evaluate the impact of these interventions to support ICT hubs on agricultural income, food security and women’s empowerment indicators. Of the total 118 hubs targeted by the project, 59 hubs were randomly selected as a treatment group (first cohort in the phased implementation) and the remaining 59 hubs as a control group (second cohort in the phased implementation). Baseline data were collected in June 2021; interventions with the first cohort hubs started in 2021 and 2022 cropping and marketing seasons; and a follow-up survey is being prepared. A total of 1,012 members of these hubs (6–10 randomly selected members in each hub) provide the sample households for the baseline and impact evaluation. Within these 1,012 sample households, one female and one male were interviewed, giving a total of 2,024 rural women and rural men as our sample respondents. Follow-up survey data were available in July and will be analyzed in time for the conference. This study will provide rigorous empirical evidence on the causal impact of digital extension, combined with group-based approaches and gender targeting.